The Treatment of Proprietary Relations in Burhan al-Din Mahmud al-Bukhari’s Zakhira (The Journal of Interdisciplinary Human Studies, 2026)
This article provides a scholarly and theoretical analysis of proprietary relations and their principal domains as presented in Zakhira, one of the significant sources of Hanafi jurisprudence authored by Burhan al-Din Mahmud al-Bukhari. The study examines the concept of property, issues of ownership and disposition, as well as the legal regulation of proprietary relations within various forms of muʿamalat, including sale, lease, loan, gift, and other transactional practices. The article substantiates the role of Zakhira in the legal systematization of proprietary relations and highlights its practical significance within economic transactions.
Keywords: proprietary relations; property rights; muʿamalat; sale; lease; loan; disposition; economic law